Synthesis and characterization of cubic-like zinc stannate powders prepared by co-precipitation method - Wanichaya Mekprasart (Science Faculty of Chiang Mai University, 2019)
Spinel-type zinc stannate (Zn2SnO4) powders were synthesized by co-precipitation method using zinc chloride and tin chloride as the precursors for Zn and Sn sources, respectively. Co-precipitation process is one of effective techniques due to non-complex system, short process time, high yield, large scale production and cost-effectiveness comparing to other methods. The influence of calcination temperature in the range of 900 °C to 1100 °C on the structure, morphologies and cation distribution were studied using various characterization techniques. A single spinel structure phase formation after-calcined powders are confirmed by X-ray diffraction (XRD) results meanwhile scanning electron microscope (SEM) showed the appearance of cubic-like shape. The aggregation of particle and strong crystallinity was distinctly increased resulting to their greater size by the effect of high calcined temperature. Moreover, the non-equilibrium site occupancy of zinc (Zn2+) and tin (Sn4+) ions was investigated through Zn K-edge and Sn L3-edge investigated by X-ray absorption (XAS) spectra via the synchrotron radiation light source. Compared with the calcined temperature sample, XANES spectra revealed that the oxidation state of Zn was +2 and Sn valence was +4 in all spinel Zn2SnO4 samples which well corresponds to the theoretical values.